Separator for lithium-sulfur battery, lithium-sulfur battery comprising same, and method for manufacturing same
By using a porous polymer substrate separator coated with polyamic acid compound with carboxyl functional groups and amide functional groups in lithium sulfur batteries, the problem of shortening of battery life caused by lithium polysulfide migration is solved, and the capacity of lithium sulfur batteries is maintained is achieved. and prolong life.
Patent Information
- Application Number
- CN202380045408.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-08-30
- Publication Date
- 2025-01-07
AI Technical Summary
The lithium polysulfide in lithium sulfur batteries dissolves from the positive electrode and migrates to the negative electrode, resulting in a shortened battery life and a reduced capacity. The existing technology has not effectively solved this problem.
A separator with a porous polymer substrate and a polyamic acid compound coated with a carboxyl functional group and an amide functional group is used to prevent the migration of lithium polysulfide to the negative electrode, thereby extending the life of the lithium sulfur battery.
By using a polyamic acid compound-coated separator, the migration of lithium polysulfides is effectively prevented, the charging and discharge capacity of lithium sulfur batteries is maintained, the battery life is extended, and the electrochemical performance is improved.
Smart Images

Figure CN119278538A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a separator capable of suppressing the migration of polysulfide eluted from a positive electrode to thereby extend the life, and a secondary battery including the separator.
[0002] This application claims priority to Korean Patent Application No. 10-2022-0110367 filed in Korea on August 31, 2022, the disclosure of which is incorporated herein by reference. Background Art
[0003] With the technological development and growing demand for mobile devices, the demand for secondary batteries as energy sources is increasing, and among secondary batteries, lithium secondary batteries are marketed and widely used due to their high energy density and operating potential, long cycle life, and low self-discharge rate.
[0004] Recently, with the increasing concern about environmental issues, many studies are underway to develop electric vehicles (EV) and hybrid electric vehicles (HEV) as an alternative to vehicles using fossil fuels such as gasoline vehicles and diesel vehicles, which are considered to be one of the main causes of air pollution. Lithium secondary batteries with high energy density, high discharge voltage and output stability are mainly studied and used as power sources for electric vehicles and hybrid electric vehicles.
[0005] A lithium secondary battery has a structure in which an electrode assembly includes a positive electrode and a negative electrode, each electrode includes an electrode collector and an active material coated on the electrode collector, a porous separator is interposed between the positive electrode and the negative electrode, and a non-aqueous electrolyte including a lithium salt wets the electrode assembly.
[0006] At present, the lithium secondary battery market is dominated by the technology of pairing of lithium cobalt oxide LiCoO2 based on the positive electrode and the graphite at the negative electrode. The rated voltage of lithium secondary battery is about 3.6 V, and the rated voltage of most other types of batteries (Ni-Cd, Ni-MH etc.) is 1.5 V. The energy density per unit volume and the energy density per unit mass are respectively about 300 to 500Wh / l and 160 to 200 Wh / kg. This value is the highest value among all batteries on the market. In addition, the self-discharge of this battery is low and has a long life (500 or 1000 cycles). Although surprising performance has been achieved, the performance difference between all lithium ion batteries is not large at present, and it is expected that improvement will only occur to a very limited extent.
[0007] Therefore, lithium-sulfur (Li-S) batteries are emerging as an alternative to known lithium-ion batteries.
[0008] In the same way as lithium-ion secondary batteries, lithium-sulfur batteries work by moving lithium ions in the electrolyte between the positive and negative electrodes. However, since lithium-sulfur batteries use sulfur alone, unlike lithium-ion secondary batteries, which aim to store energy by inserting lithium ions into the molecules of the electrode active material, thereby causing changes in the electrode structure, lithium-sulfur batteries work based on the oxidation and reduction reactions between sulfur and lithium ions. Therefore, compared with lithium-ion secondary batteries, lithium-sulfur batteries may have a theoretically higher capacity at the same volume without being restricted by the electrode structure. Due to this feature, in a lithium-sulfur battery comprising a sulfur positive electrode and a lithium metal negative electrode, when it is assumed that elemental sulfur (S8) with a ring structure is completely reduced to lithium polysulfide (Li2S), the theoretical capacity is 1,675 mAh / g, and the theoretical energy density is 2,600 Wh / kg, which is 3 to 6 times higher than other existing battery systems (Ni / MH battery: 450 Wh / kg; Li / FeS: 480 Wh / kg; Li / MnO2: 1,000 Wh / kg; Na / S: 800 Wh / kg).
[0009] On the other hand, existing transition metal oxide-based lithium ion secondary batteries can be considered as batteries containing heavy metal pollution source materials because they contain oxides of nickel (Ni), cobalt (Co) and manganese (Mn) in the positive electrode with a density higher than the density of heavy metals (metals above 5 g / mL). However, lithium-sulfur batteries do not contain materials that cause pollution and contain non-toxic materials, and from this point of view, they are considered to be environmentally friendly. In addition, sulfur, the positive electrode material, is abundant on the earth and inexpensive.
[0010] On the other hand, in a lithium-sulfur battery, a reduction reaction of sulfur and an oxidation reaction of lithium metal occur during discharge, in which case sulfur forms a linear structure of lithium polysulfide (LiPS) from a ring structure of S8, and the lithium-sulfur battery exhibits a step-type discharge voltage until the lithium polysulfide is completely reduced to Li2S. However, when the lithium-sulfur battery is charged and discharged, the charge and discharge efficiency decreases, and the battery life is shortened. As described above, the shortened life of the lithium-sulfur battery is caused by many different factors, such as side reactions of the electrolyte, instability of lithium metal, and accumulation of positive electrode byproducts (e.g., dissolution of lithium polysulfide from the positive electrode).
[0011] That is, in a lithium-sulfur battery using a sulfur compound as a positive electrode active material and an alkali metal such as lithium as a negative electrode active material, dissolution of lithium polysulfide occurs during charge and discharge, and the lithium polysulfide dissolved from the positive electrode migrates to the negative electrode, thereby reducing the capacity of the lithium-sulfur battery and shortening the life of the lithium-sulfur battery. That is, since the lithium polysulfide dissolved from the positive electrode has a high solubility in the electrolyte, the lithium polysulfide may migrate to the negative electrode through the electrolyte by itself through the separator, causing irreversible loss of the positive electrode active material and the resulting capacity reduction, as well as accumulation of sulfur particles on the surface of the lithium metal caused by side reactions, thereby shortening the battery life.
[0012] In order to solve the problem of shortened life caused by lithium polysulfides, in the technical field, research has been conducted on adding lithium polysulfide absorbing materials to the positive electrode composite or adding reaction moderation materials to the negative electrode to prevent side reactions on the lithium metal surface, but no meaningful results have been produced. Summary of the invention
[0013] Technical issues
[0014] One embodiment of the present disclosure is to provide a separator capable of preventing lithium polysulfide from being dissolved from a positive electrode and migrating to a negative electrode, thereby improving the life of a lithium-sulfur battery.
[0015] Another embodiment of the present disclosure is directed to providing a lithium-sulfur battery including the separator.
[0016] Another embodiment of the present disclosure is directed to providing a method for manufacturing the separator.
[0017] Furthermore, it is easily understood that these and other objects and advantages of the present disclosure can be achieved by the means or methods set forth in the appended claims, and combinations thereof.
[0018] Technical Solution
[0019] In order to solve the above-mentioned problems of the present disclosure, a separator, a lithium-sulfur battery including the separator, and a method of manufacturing the separator according to the following embodiments are provided.
[0020] According to a first embodiment, there is provided a separator for a lithium-sulfur battery, comprising a porous polymer substrate having a plurality of pores; and a coating on at least one surface of the porous polymer substrate, the coating comprising a polyamic acid compound having a carboxyl functional group and an amide functional group, wherein the molar ratio of the carboxyl functional group to the amide functional group is 1:0.5 to 1:5.
[0021] According to a second embodiment, in the first embodiment, a molar ratio of the carboxyl functional group to the amide functional group may be 1:0.75 to 1:3.
[0022] According to a third embodiment, in the first or second embodiment, the polyamic acid compound may be a polymer including a unit having the carboxyl functional group and the amide functional group as a repeating unit.
[0023] According to a fourth embodiment, in any one of the first to third embodiments, the molar concentration (mmol / L) of the carboxyl functional groups may be 5 to 15, and the molar concentration of the amide functional groups may be 8 to 20.
[0024] According to a fifth embodiment, in any one of the first to fourth embodiments, the polyamic acid compound may be an aromatic polyamic acid compound.
[0025] According to a sixth embodiment, in any one of the first to fifth embodiments, the polyamic acid may have a polydispersity index (PDI) of 2.6 to 3.2.
[0026] According to a seventh embodiment, in any one of the first to sixth embodiments, the polyamic acid compound having a carboxyl functional group and an amide functional group may be present in pores of the porous polymer substrate.
[0027] According to an eighth embodiment, there is provided a lithium-sulfur battery including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, wherein the separator is the separator for a lithium-sulfur battery according to any one of the first to sixth embodiments.
[0028] According to a ninth embodiment, there is provided a method for manufacturing a separator for a lithium-sulfur battery, the method comprising preparing a porous polymer substrate having a plurality of pores; and forming a coating layer comprising a polyamic acid compound having a carboxyl functional group and an amide functional group on at least one surface of the porous polymer substrate, wherein the formation of the coating layer comprising the polyamic acid compound comprises immersing the porous polymer substrate in a first solution comprising a carboxylic dianhydride compound; and immersing the porous polymer substrate immersed in the first solution in a second solution comprising a diamine compound, and wherein a molar ratio of the carboxyl functional group to the amide functional group is 1:0.5 to 1:5.
[0029] According to the tenth embodiment, in the ninth embodiment, when the coating layer containing the polyamic acid compound is formed on the at least one surface of the porous polymer substrate, the coating layer of the polyamic acid compound may be formed on the at least one surface of the porous polymer substrate, and at the same time, the polyamic acid compound may be present in the pores.
[0030] According to an eleventh embodiment, in the ninth or tenth embodiment, a molar ratio of the carboxyl functional group to the amide functional group may be 1:0.75 to 1:3.
[0031] According to a twelfth embodiment, in any one of the ninth to eleventh embodiments, the amount of the carboxylic dianhydride compound in the first solution may be 0.2 to 3 wt %, and the amount of the diamine compound in the second solution may be 0.2 to 3 wt %.
[0032] According to a thirteenth embodiment, in any one of the ninth to twelfth embodiments, the carboxyl functional group may be derived from the carboxylic dianhydride compound, and the amide functional group may be derived from the diamine compound.
[0033] According to the fourteenth embodiment, in the thirteenth embodiment, the carboxylic acid dianhydride compound may include at least one of the following: 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-diphenyl tetracarboxylic dianhydride, 3,3',4,4'-diphenyl sulfone tetracarboxylic dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, 1,2,3,4-benzene tetracarboxylic dianhydride, methylcyclohexene tetracarboxylic dianhydride, naphthalene-1,4,5,8-tetracarboxylic dianhydride or ethylene tetracarboxylic dianhydride. Acid dianhydride, and the diamine compound may include at least one of the following: p-phenylenediamine, m-phenylenediamine, 2,2'-bis(trifluoromethyl)-4,4'-biphenylenediamine, 2,2'-dimethyl-4,4'-diaminobenzidine, 4,4'-diaminodiphenyl sulfone, 2,7-diaminofluorene, 4,4-diaminooctafluorobiphenyl, 4,4'-oxydiphenylamine, 2,2'-dimethyl-4,4'-diaminobiphenyl, m-xylylenediamine, p-xylylenediamine or 4,4'-diaminobenzanilide.
[0034] According to a fifteenth embodiment, in any one of the ninth to fourteenth embodiments, immersing the porous polymer substrate in the first solution and immersing the porous polymer substrate in the second solution may each be performed for 40 minutes to 80 minutes.
[0035] According to a sixteenth embodiment, in the fifteenth embodiment, the method for manufacturing a separator for a lithium-sulfur battery may further include, after immersing the porous polymer substrate in the second solution, cleaning the porous polymer substrate; and drying the cleaned porous polymer substrate in a vacuum.
[0036] Beneficial Effects
[0037] The lithium-sulfur battery separator according to an embodiment of the present disclosure has the coating layer containing the polyamic acid compound on at least one surface of the porous polymer substrate by immersing the porous polymer substrate in the first solution containing the carboxylic dianhydride compound and then in the second solution containing the diamine compound. The polyamic acid compound contains the carboxyl functional group and the amide functional group, and the molar ratio of the carboxyl functional group to the amide functional group is 1:0.5 to 1:5. Since the separator has the coating layer containing the polyamic acid compound, the lithium polysulfide dissolved from the positive electrode of the lithium-sulfur battery can be prevented from migrating to the negative electrode. Therefore, the sulfur particles can be prevented from accumulating on the lithium metal surface of the negative electrode, thereby maintaining the charge and discharge capacity of the lithium-sulfur battery and improving the battery life.
[0038] In addition, the polyamic acid of the coating is made by in-situ polymerization. First, the carboxylic acid dianhydride compound of the monomolecular state is provided to the porous polymer substrate, so the carboxylic acid dianhydride compound can be applied to the hole of the porous polymer substrate. Subsequently, the diamine compound is provided, thereby causing polymerization reaction in the hole, so the polyamic acid compound can be applied to the hole. In addition, the interface resistance between the coating and the porous polymer substrate can also be reduced, thereby achieving higher electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The accompanying drawings illustrate exemplary embodiments of the present disclosure and, together with the following detailed description, serve to provide a further understanding of the technical aspects of the present disclosure, and thus the present disclosure should not be construed as being limited to the accompanying drawings.
[0040] Figure 1 is a diagram illustrating a method of manufacturing a separator for a lithium-sulfur battery according to one embodiment of the present disclosure.
[0041] Figure 2 is a diagram showing a method for producing a lithium-sulfur battery separator according to Example 1.
[0042] Figure 3 and Figure 4 is a graph showing the discharge capacity of a lithium-sulfur battery including a lithium-sulfur battery separator obtained by the manufacturing method according to an example of the present disclosure and a lithium-sulfur battery separator according to a comparative example.
[0043] Figure 5 and Figure 6 : is a graph showing the results of thermal stability evaluation of the separators according to Example 1 and Comparative Example 1.
[0044] Figure 7 Graphs showing suppression of polysulfide dissolution in the separators of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0045] The present disclosure will be described in more detail below.
[0046] It should be understood that the terms or words used in this specification and the appended claims should not be interpreted as limited to the general meaning and dictionary meaning, but should be interpreted based on the principle of allowing the inventor to appropriately define the terms for the best explanation, based on the meaning and concepts corresponding to the technical aspects of the present disclosure.
[0047] When used in this specification, unless the context clearly indicates otherwise, the terms “comprising” or “including” specify the presence of stated elements, but do not exclude the presence or addition of one or more other elements.
[0048] The terms "about" or "approximately" are used herein in the sense of equal or approximately when given inherent manufacturing and material tolerances in the stated circumstances, and are used to prevent unscrupulous infringers from taking unfair advantage of the disclosure where exact or absolute numbers are stated to aid in a better understanding of the disclosure.
[0049] The present disclosure relates to a diaphragm, an electrochemical cell comprising the diaphragm, and a method for manufacturing the diaphragm. In the present disclosure, the electrochemical cell may include any type of battery that produces an electrochemical reaction. Specific examples of the electrochemical cell include any type of primary battery, secondary battery, fuel cell, solar cell, and capacitor such as a supercapacitor, etc. In particular, the electrochemical cell may be a secondary battery, and the secondary battery may be a lithium ion secondary battery. The lithium ion secondary battery may include, for example, a lithium metal battery, a lithium sulfur battery, an all-solid-state battery, a lithium polymer battery, etc., wherein a lithium sulfur battery is preferred.
[0050] Among secondary batteries, lithium-sulfur batteries have high discharge capacity and theoretical energy density, and since sulfur used as a positive electrode active material is abundant on earth and inexpensive, lithium-sulfur batteries have low battery manufacturing costs and are environmentally friendly, so they are attracting attention as next-generation secondary batteries.
[0051] In the present disclosure, the positive electrode active material comprises a carbon-sulfur composite, and the carbon-sulfur composite comprises a porous carbon material. In the lithium-sulfur battery, since the positive electrode active material sulfur is non-conductive, a carbon-sulfur composite in which a conductive material such as a carbon material is combined with sulfur is generally used to improve conductivity.
[0052] According to one aspect of the present disclosure, a separator for a lithium-sulfur battery is provided, the separator for a lithium-sulfur battery comprising:
[0053] a porous polymer substrate having a plurality of pores; and
[0054] a coating on at least one surface of the porous polymer substrate, the coating comprising a polyamic acid compound having a carboxyl functional group and an amide functional group,
[0055] The molar ratio of the carboxyl functional group to the amide functional group is 1:0.5 to 1:5.
[0056] The porous polymer substrate is not limited to a specific type and may include any type of material that can be used as a separator material for an electrochemical device to electrically insulate the negative electrode from the positive electrode, thereby preventing short circuits and providing a path for the movement of lithium ions. The porous polymer substrate may include, for example, a porous polymer film or a non-woven fabric containing at least one of a polymer resin such as polyolefin, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalate.
[0057] The coating is located on at least one surface of the porous polymer substrate and comprises the polyamic acid compound having a carboxyl functional group and an amide functional group. The carboxyl functional group may be derived from a carboxylic dianhydride compound, and the amide functional group may be derived from a diamine compound.
[0058] In the lithium-sulfur battery, a reduction reaction of sulfur and an oxidation reaction of lithium metal occur during discharge, in which case sulfur forms a linear structure of lithium polysulfide (LiPS) from a ring structure of S8, and the lithium-sulfur battery exhibits a step-type discharge voltage until the lithium polysulfide is completely reduced to Li2S.
[0059] However, during the charge and discharge process, the charge and discharge efficiency of the lithium-sulfur battery decreases and the battery life is shortened. As described above, the shortened life of the lithium-sulfur battery is caused by many different factors, such as side reactions of the electrolyte, instability of lithium metal, and accumulation of positive electrode byproducts (e.g., dissolution of lithium polysulfide from the positive electrode).
[0060] That is, in a lithium-sulfur battery using a sulfur compound as a positive electrode active material and an alkali metal such as lithium as a negative electrode active material, dissolution of lithium polysulfide occurs during charge and discharge, and the lithium polysulfide dissolved from the positive electrode migrates to the negative electrode, thereby reducing the capacity of the lithium-sulfur battery and shortening the life of the lithium-sulfur battery. That is, since the lithium polysulfide dissolved from the positive electrode has a high solubility in the electrolyte, the lithium polysulfide may migrate to the negative electrode through the electrolyte by itself through the separator, causing irreversible loss of the positive electrode active material and the resulting capacity reduction, as well as accumulation of sulfur particles on the surface of the lithium metal caused by side reactions, thereby shortening the battery life.
[0061] In order to solve the problem of shortened life caused by lithium polysulfides, in the technical field, research has been conducted on adding lithium polysulfide absorbing materials to the positive electrode composite or adding reaction moderation materials to the negative electrode to prevent side reactions on the lithium metal surface, but no meaningful results have been produced.
[0062] Therefore, in order to prevent the lithium polysulfide dissolved from the positive electrode from migrating to the negative electrode and accumulating on the surface of the negative electrode, the present disclosure discloses a separator for a lithium-sulfur battery, which has a coating layer containing a polyamic acid compound having a carboxyl functional group and an amide functional group on at least one surface of the porous polymer substrate. Since the polyamic acid compound having a carboxyl functional group and an amide functional group is coated on the porous polymer substrate, the lithium polysulfide dissolved from the positive electrode can be prevented from migrating to the negative electrode, thereby improving the life of the lithium-sulfur battery.
[0063] According to one embodiment of the present disclosure, the coating layer including the polyamic acid compound may be formed on the porous polymer substrate, and the polyamic acid compound having a carboxyl functional group and an amide functional group may exist in pores of the porous polymer substrate.
[0064] In one embodiment, the polyamic acid compound can be a polymer comprising a unit having a carboxyl functional group and an amide functional group as a repeating unit. In addition, the polyamic acid compound can include an aromatic polyamic acid compound, an aliphatic polyamic acid compound, and an aliphatic cyclic polyamic acid compound, and in the present disclosure, in order to carry out a more uniform and smooth coating on the porous polymer substrate, an aromatic polyamic acid compound having a phenol group that can form a π-π bond with the pores of the porous polymer substrate can be selected.
[0065] According to one embodiment of the present disclosure, the polyamic acid compound may include a chemical structure represented by the following Formula 1. Alternatively, the polyamic acid compound may include a repeating unit represented by the following Formula 1.
[0066] [Formula 1]
[0067]
[0068] In Formula 1 above, A1 is a tetravalent organic group having 1 to 20 carbon atoms, and A2 is a divalent organic group having 1 to 20 carbon atoms.
[0069] For example, A1 may be a tetravalent aliphatic organic group having 1 to 20 carbon atoms, a tetravalent alicyclic organic group having 3 to 20 carbon atoms, or a tetravalent aromatic organic group having 6 to 20 carbon atoms.
[0070] For example, A2 may be a divalent aliphatic organic group having 1 to 20 carbon atoms, a divalent alicyclic organic group having 3 to 20 carbon atoms, or a divalent aromatic organic group having 6 to 20 carbon atoms.
[0071] According to one embodiment of the present disclosure, the polyamic acid compound may include a chemical structure represented by the following Formula 2. Alternatively, the polyamic acid compound may include a repeating unit represented by the following Formula 2.
[0072] [Formula 2]
[0073]
[0074] In Formula 2 above, Ar1 is a tetravalent aromatic organic group having 6 to 20 carbon atoms, and Ar2 is a divalent aromatic organic group having 6 to 20 carbon atoms.
[0075] According to one embodiment of the present disclosure, the polyamic acid compound may be benzophenone polyamic acid (BPAA) having a structure of the following Formula 3, or may be naphthalene polyamic acid or pyrene polyamic acid.
[0076] [Formula 3]
[0077]
[0078] In Formula 3 above, n may be an integer of about 3 to 12 or about 5 to 10.
[0079] In the polyamic acid compound of the present disclosure, the molar ratio of the carboxyl functional group to the amide functional group is 1:0.5 to 1:5. According to one embodiment of the present disclosure, the molar ratio of the carboxyl functional group to the amide functional group may be about 1:0.75 to 1:3, about 1:0.8 to 1:2, or about 1:1 to 1:1.5.
[0080] When the molar ratio of the carboxyl functional group to the amide functional group satisfies the above range, the lithium polysulfide dissolved from the positive electrode can be prevented from migrating to the negative electrode, thereby improving the life of the lithium-sulfur battery. When the molar ratio of the carboxyl functional group to the amide functional group is less than 1:0.5 or greater than 1:5, the lithium polysulfide dissolved from the positive electrode cannot be prevented from migrating to the negative electrode, thereby failing to improve the life of the lithium-sulfur battery.
[0081] According to one embodiment of the present disclosure, the molar concentration (mmol / L) of the carboxyl functional group may be about 5 to 15 or about 5 to 8, and the molar concentration (mmol / L) of the amide functional group may be about 8 to 20 or about 8 to 12. When the molar concentrations (mmol / L) of the carboxyl functional group and the amide functional group satisfy the above ranges, it may be possible to prevent the penetration of lithium polysulfide, thereby improving battery life.
[0082] The molar concentration and molar ratio of the carboxyl functional group and the amide functional group can be measured using a variety of measurement methods known in the art. For example, the molar concentration and molar ratio of the carboxyl functional group and the amide functional group can be measured using a 1H-nuclear magnetic resonance (NMR) spectrometer under the following conditions.
[0083] -Instrument: AVANCE AC 400FT NMR spectrometer (Bruker)
[0084] -Measurement frequency: 400 MHz
[0085] -Measurement solvent: DMSO-d6
[0086] -Measurement temperature: 25℃
[0087] In addition, the weight average molecular weight of the polyamic acid compound may be about 1,000 to 5,000 or about 4,000 to 5,000, and the polydispersity index (PDI, a measure of molecular weight distribution) may be about 2.6 to 3.2 or about 2.7 to 2.9. When the weight average molecular weight and PDI of the polyamic acid compound meet the above ranges, it may be possible to prevent the penetration of lithium polysulfide, thereby improving battery life.
[0088] In this case, the weight average molecular weight and PDI can be measured using gel permeation chromatography. Specifically, the PDI can be calculated by measuring the number average molecular weight (Mn) and the weight average molecular weight (Mw) by gel permeation chromatography (GPC, PL GPC220, Agilent Technologies) under the following conditions, and dividing the weight average molecular weight by the number average molecular weight.
[0089] - Column: PL MiniMixed B x 2
[0090] - Solvent: Tetrahydrofuran (THF)
[0091] - Flow rate: 0.3 ml / min
[0092] - Sample concentration: 2.0 mg / ml
[0093] - Injection volume: 10 μL
[0094] - Column temperature: 40°C
[0095] - Detector: Agilent RI detector
[0096] - Standard: Polystyrene (fitted to a cubic polynomial)
[0097] - Data processing: ChemStation
[0098] In addition, according to a specific embodiment of the present disclosure, the lithium-sulfur battery separator may further include an organic / inorganic composite porous coating layer. The organic / inorganic composite porous coating layer may be located on at least one surface of the porous polymer substrate and include a plurality of inorganic particles and a binder.
[0099] According to one aspect of the present disclosure, there is provided a method for manufacturing the separator for a lithium-sulfur battery, the method comprising:
[0100] preparing a porous polymer substrate having a plurality of pores; and
[0101] forming a coating layer comprising a polyamic acid compound having a carboxyl functional group and an amide functional group on at least one surface of the porous polymer substrate,
[0102] The formation of the coating layer containing the polyamic acid compound includes:
[0103] immersing the porous polymer substrate in a first solution comprising the carboxylic dianhydride compound; and
[0104] The porous polymer substrate immersed in the first solution is immersed in a second solution containing the diamine compound, and
[0105] The molar ratio of the carboxyl functional group to the amide functional group is 1:0.75 to 1:3.
[0106] According to one embodiment of the present disclosure, when a coating layer including a polyamic acid compound is formed on at least one surface of the porous polymer substrate, the coating layer of the polyamic acid compound may be formed on at least one surface of the porous polymer substrate, and at the same time, the polyamic acid compound may be present in the pores.
[0107] A method for manufacturing a separator for a lithium-sulfur battery according to one specific embodiment of the present disclosure will be described below.
[0108] Figure 1 is a diagram illustrating a method of manufacturing a separator for a lithium-sulfur battery according to one embodiment of the present disclosure.
[0109] refer to Figure 1 , the porous polymer substrate 100 may be prepared. As described above, the porous polymer substrate 100 may include a porous polymer film or a non-woven fabric, and the porous polymer film or the non-woven fabric includes at least one of polymer resins such as polyolefin, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene oxide, polyphenylene sulfide, and polyethylene naphthalate.
[0110] Subsequently, the porous polymer substrate 100 can be immersed in the first solution (SOL1). For example, the porous polymer substrate 100 can be immersed in the first solution (SOL1) for about 40 minutes to 80 minutes. The first solution (SOL1) can include the carboxylic acid dianhydride compound, specifically the carboxylic acid dianhydride compound and the first solvent, and the first solvent can include n-methylpyrrolidone (NMP), tetrahydrofuran (THF), dimethylformamide (DMF), acetone, ethanol, water or a mixture of two or more thereof. The amount of the carboxylic acid dianhydride compound in the first solution (SOL1) can be about 0.2 wt % to 3 wt % or about 0.5 wt % to 1 wt %.
[0111] In one embodiment, the carboxylic acid dianhydride compound may include at least one of the following: 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-diphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, 1,2,3,4-benzenetetracarboxylic dianhydride, methylcyclohexenetetracarboxylic dianhydride, naphthalene-1,4,5,8-tetracarboxylic dianhydride or ethylenetetracarboxylic dianhydride.
[0112] For example, the carboxylic acid dianhydride compound may include 3,3′,4,4′-benzophenonetetracarboxylic acid dianhydride (BPTCDA).
[0113] The porous polymer substrate 100 immersed in the first solution (SOL1) can be immersed in the second solution (SOL2). For example, the porous polymer substrate 100 can be immersed in the second solution (SOL2) for about 40 minutes to 80 minutes. In one embodiment, the second solution (SOL2) can include the diamine compound, specifically the diamine compound and a second solvent, and the second solvent can include n-methylpyrrolidone (NMP), tetrahydrofuran (THF), dimethylformamide (DMF), acetone, ethanol, water or a mixture of two or more thereof. The amount of the diamine compound in the second solution (SOL2) can be about 0.2 wt % to 3 wt % or about 0.5 wt % to 1 wt %.
[0114] In one embodiment, the diamine compound may include at least one of p-phenylenediamine, m-phenylenediamine, 2,2'-bis(trifluoromethyl)-4,4'-biphenylenediamine, 2,2'-dimethyl-4,4'-diaminobenzidine, 4,4'-diaminodiphenyl sulfone, 2,7-diaminofluorene, 4,4-diaminooctafluorobiphenyl, 4,4'-oxydiphenylamine, 2,2'-dimethyl-4,4'-diaminobiphenyl, m-xylylenediamine, p-xylylenediamine or 4,4'-diaminobenzanilide.
[0115] For example, the diamine compound may include p-phenylenediamine (PDA).
[0116] The polyamic acid (e.g., Figure 1 In this case, the process of dipping the porous polymer substrate 100 in the first solution (SOL1) and the second solution (SOL2) can be appropriately set based on the coating properties of the compound on the porous polymer substrate 100.
[0117] In one embodiment, after the porous polymer substrate 100 is immersed in the first solution (SOL1), the second solution (SOL2) can be injected into the porous polymer substrate 100 immersed in the first solution (SOL1) to immerse the porous polymer substrate 100 in the second solution (SOL2).
[0118] In another embodiment, after the porous polymer substrate 100 is immersed in the first solution (SOL1), the porous polymer substrate 100 coated with the first solution (SOL1) may be taken out and then immersed in the second solution (SOL2).
[0119] In addition, the order of immersing the porous polymer substrate 100 in the first solution ( SOL1 ) and the second solution ( SOL2 ) may be appropriately set.
[0120] In one embodiment, the porous polymer substrate 100 may be first immersed in the first solution (SOL1) and then immersed in the second solution (SOL2). In this case, the carboxylic acid dianhydride compound contained in the first solution (SOL1) may have a large number of phenol groups and form a π-π bond with the porous polymer substrate 100. Therefore, since the porous polymer substrate 100 is first immersed in the first solution (SOL1) having a large number of phenol groups, the bonding strength between the porous polymer substrate 100 and the first solution (SOL1) may be increased.
[0121] However, the present disclosure is not limited thereto, and in another embodiment, the porous polymer substrate 100 may be firstly immersed in the second solution ( SOL2 ).
[0122] Subsequently, the porous polymer substrate 100 may be cleaned and dried for about 24 hours to remove unreacted substances remaining on the surface of the porous polymer substrate 100. For example, the porous polymer substrate 100 may be cleaned by a cleaning agent such as ethanol and dried in a vacuum.
[0123] The polyamic acid of the coating according to the embodiment of the present disclosure can be made by in-situ polymerization. For example, the carboxylic acid dianhydride compound with a carboxyl functional group can be first provided to the porous polymer substrate 100, and then the diamine compound with an amine functional group can be provided. Since the carboxylic acid dianhydride compound in a single molecule state is first provided to the porous polymer substrate 100, the carboxylic acid dianhydride compound can be uniformly applied to the holes of the porous polymer substrate 100. Subsequently, the diamine compound can be provided, thereby causing a polymerization reaction in the hole, so that the polyamic acid compound can be more uniformly applied to the hole. In addition, the interface resistance between the coating and the porous polymer substrate 100 can be reduced, thereby achieving higher electrochemical performance.
[0124] In addition, the carboxyl functional group and the amide functional group are present in the polyamic acid of the coating according to the embodiment of the present disclosure. In other words, polyimide can be synthesized by imidization of polyamic acid, and the coating of the present disclosure contains unimidized polyamic acid. Therefore, the carboxyl functional group and the amide functional group may still be present in the polyamic acid of the coating, and the separator having the coating may inhibit the migration of lithium polysulfide, thereby increasing the life of the lithium-sulfur battery.
[0125] Embodiments will be described in detail below to help better understand the present disclosure. However, embodiments according to the present disclosure can be modified in many other forms, and the scope of the present disclosure should not be considered to be limited to the following embodiments. The embodiments of the present disclosure are provided to fully explain the present disclosure to those of ordinary skill in the art.
[0126] Example 1
[0127] positive electrode
[0128] As for the positive electrode active material, a carbon-sulfur composite in which carbon nanotubes (CNT) and sulfur (S) were mixed in a weight ratio of 1:3 was used. The carbon-sulfur composite was mixed with a PAA binder in a weight ratio of 96:4 to prepare a positive electrode slurry, which was uniformly coated on an aluminum foil to a thickness of 300 μm, dried at 55°C and cut into a diameter of 11 μm to prepare a positive electrode.
[0129] Anode and electrolyte
[0130] As the negative electrode, lithium metal was used, and 1.0 M LiNO3 was added to a mixed solvent of 1,3-dioxolane (DOL) and 1,2-dimethyl ether in a volume ratio (v / v) of 50:50 to prepare an electrolyte for a lithium-sulfur secondary battery.
[0131] Diaphragm
[0132] Figure 2 The process of manufacturing the separator of Example 1 is shown.
[0133] refer to Figure 2 A polyethylene porous membrane (Celgard 2320) was prepared as a porous polymer substrate, a first solution (SOL1) containing 1 wt % of 3,3'4,4'-benzophenonetetracarboxylic dianhydride (BPTCDA) as a carboxylic dianhydride compound in n-methylpyrrolidone (NMP) as a first solvent was prepared, and a second solution (SOL2) containing 1 wt % of p-phenylenediamine (p-PDA) as a diamine compound in ethanol as a second solvent was prepared.
[0134] First, the porous polymer substrate was immersed in the prepared first solution (SOL1) for 1 hour, and the second solution (SOL2) was injected into the porous polymer substrate. As a result, a separator having a coating layer containing benzophenone polyamic acid (BPAA) prepared by in-situ polymerization on both surfaces of the porous polymer substrate was prepared.
[0135] In this case, in the benzophenone polyamic acid (BPAA), the molar concentration (mmol / L) of the carboxyl functional group is 6.27, and the molar concentration (mmol / L) of the amide functional group is 9.34. Therefore, the molar ratio of the carboxyl functional group to the amide functional group is 1:1.5.
[0136] A 2032 coin-type lithium-sulfur battery was prepared using the positive electrode, the negative electrode, the electrolyte and the separator.
[0137] Example 2
[0138] Positive electrode, negative electrode and electrolyte
[0139] In the same manner as in Example 1, a positive electrode, a negative electrode, and an electrolyte were prepared.
[0140] Diaphragm
[0141] A polyethylene porous membrane (Celgard 2320) was prepared as a porous polymer substrate, a first solution containing 0.5 wt % of 3,3'4,4'-benzophenonetetracarboxylic dianhydride (BPTCDA) as a carboxylic dianhydride compound in n-methylpyrrolidone (NMP) as a first solvent was prepared, and a second solution containing 1 wt % of p-phenylenediamine (p-PDA) as a diamine compound in ethanol as a second solvent was prepared.
[0142] First, the porous polymer substrate was immersed in the prepared first solution for 1 hour, and the second solution was injected into the porous polymer substrate. As a result, a separator having a coating layer containing benzophenone polyamic acid (BPAA) prepared by in-situ polymerization on both surfaces of the porous polymer substrate was prepared.
[0143] In this case, in the benzophenone polyamic acid (BPAA), the molar concentration (mmol / L) of the carboxyl functional group is 6.27, and the molar concentration (mmol / L) of the amide functional group is 18.68. Therefore, the molar ratio of the carboxyl functional group to the amide functional group is 1:3.
[0144] A 2032 coin-type lithium-sulfur battery was prepared using the positive electrode, the negative electrode, the electrolyte and the separator.
[0145] Example 3
[0146] Positive electrode, negative electrode and electrolyte
[0147] In the same manner as in Example 1, a positive electrode, a negative electrode, and an electrolyte were prepared.
[0148] Diaphragm
[0149] A polyethylene porous membrane (Celgard 2320) was prepared as a porous polymer substrate, a first solution containing 1 wt% of 3,3'4,4'-benzophenonetetracarboxylic dianhydride (BPTCDA) as a carboxylic dianhydride compound in n-methylpyrrolidone (NMP) as a first solvent was prepared, and a second solution containing 0.5 wt% of p-phenylenediamine (p-PDA) as a diamine compound in ethanol as a second solvent was prepared.
[0150] First, the porous polymer substrate was immersed in the prepared first solution for 1 hour, and the second solution was injected into the porous polymer substrate. As a result, a separator having a coating layer containing benzophenone polyamic acid (BPAA) prepared by in-situ polymerization on both surfaces of the porous polymer substrate was prepared.
[0151] In this case, in the benzophenone polyamic acid (BPAA), the molar concentration (mmol / L) of the carboxyl functional group is 12.54, and the molar concentration (mmol / L) of the amide functional group is 9.34. Therefore, the molar ratio of the carboxyl functional group to the amide functional group is 1:0.75.
[0152] A 2032 coin-type lithium-sulfur battery was prepared using the positive electrode, the negative electrode, the electrolyte and the separator.
[0153] Comparative Example 1
[0154] Positive electrode, negative electrode and electrolyte
[0155] In the same manner as in Example 1, a positive electrode, a negative electrode, and an electrolyte were prepared.
[0156] Diaphragm
[0157] As the porous polymer substrate, a polyethylene porous film (Celgard 2320) was used, and a separator not coated with a coating layer containing polyamic acid was used.
[0158] A 2032 coin-type lithium-sulfur battery was prepared using the positive electrode, the negative electrode, the electrolyte and the separator.
[0159] Comparative Example 2
[0160] Positive electrode, negative electrode and electrolyte
[0161] In the same manner as in Example 1, a positive electrode, a negative electrode, and an electrolyte were prepared.
[0162] Diaphragm
[0163] A polyethylene porous membrane (Celgard 2320) was prepared as a porous polymer substrate, a first solution containing 5 wt% of 3,3'4,4'-benzophenonetetracarboxylic dianhydride (BPTCDA) as a carboxylic dianhydride compound in n-methylpyrrolidone (NMP) as a first solvent was prepared, and a second solution containing 1 wt% of p-phenylenediamine (p-PDA) as a diamine compound in ethanol as a second solvent was prepared.
[0164] First, the porous polymer substrate was immersed in the prepared first solution for 1 hour, and the second solution was injected into the porous polymer substrate. As a result, a separator having a coating layer containing benzophenone polyamic acid (BPAA) prepared by in-situ polymerization on both surfaces of the porous polymer substrate was prepared.
[0165] In this case, in the benzophenone polyamic acid (BPAA), the molar concentration (mmol / L) of the carboxyl functional group is 62.69, and the molar concentration (mmol / L) of the amide functional group is 18.68. Therefore, the molar ratio of the carboxyl functional group to the amide functional group is 1:0.3.
[0166] A 2032 coin-type lithium-sulfur battery was prepared using the positive electrode, the negative electrode, the electrolyte and the separator.
[0167] Comparative Example 3
[0168] Positive electrode, negative electrode and electrolyte
[0169] In the same manner as in Example 1, a positive electrode, a negative electrode, and an electrolyte were prepared.
[0170] Diaphragm
[0171] A first solution containing 1 wt % of 3,3'4,4'-benzophenonetetracarboxylic dianhydride (BPTCDA) as a carboxylic dianhydride compound in n-methylpyrrolidone (NMP) as a first solvent and a second solution containing 1 wt % of p-phenylenediamine (p-PDA) as a diamine compound in ethanol as a second solvent are mixed to prepare a mixed solution, and the mixed solution is coated on both surfaces of a polyethylene porous membrane (Celgard 3230) as a porous polymer substrate to prepare a separator having a coating layer containing benzophenone polyamic acid (BPAA) produced by non-in situ polymerization on both surfaces of the porous polymer substrate.
[0172] In this case, in the benzophenone polyamic acid, the molar concentration (mmol / L) of the carboxyl functional group is 6.27, and the molar concentration (mmol / L) of the amide functional group is 9.34. Therefore, the molar ratio of the carboxyl functional group to the amide functional group is 1:1.5.
[0173] A 2032 coin-type lithium-sulfur battery was prepared using the positive electrode, the negative electrode, the electrolyte and the separator.
[0174] Comparative Example 4
[0175] Positive electrode, negative electrode and electrolyte
[0176] In the same manner as in Example 1, a positive electrode, a negative electrode, and an electrolyte were prepared.
[0177] Diaphragm
[0178] A polyethylene porous membrane (Celgard 2320) was prepared as a porous polymer substrate, a first solution containing 5 wt% of 3,3'4,4'-benzophenonetetracarboxylic dianhydride (BPTCDA) as a carboxylic dianhydride compound in n-methylpyrrolidone (NMP) as a first solvent was prepared, and a second solution containing 1 wt% of p-phenylenediamine (p-PDA) as a diamine compound in ethanol as a second solvent was prepared.
[0179] First, the porous polymer substrate was immersed in the prepared first solution for 1 hour, and the second solution was injected into the porous polymer substrate. As a result, a separator having a coating layer containing benzophenone polyamic acid (BPAA) prepared by in-situ polymerization on both surfaces of the porous polymer substrate was prepared.
[0180] In this case, in the benzophenone polyamic acid (BPAA), the molar concentration (mmol / L) of the carboxyl functional group is 6.27, and the molar concentration (mmol / L) of the amide functional group is 37.62. Therefore, the molar ratio of the carboxyl functional group to the amide functional group is 1:6.
[0181] A 2032 coin-type lithium-sulfur battery was prepared using the positive electrode, the negative electrode, the electrolyte and the separator.
[0182] Evaluation results
[0183] 1. Measurement of the molar concentration and molar ratio of carboxyl and amide functional groups
[0184] The molar concentration and molar ratio of the carboxyl functional group and the amide functional group of the polyamic acid compound contained in the coating layers of the separators prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were measured using a 1 H-NMR spectrometer under the following conditions.
[0185] -Instrument: AVANCE AC 400FT NMR spectrometer (Bruker)
[0186] -Measurement frequency: 400 MHz
[0187] -Measurement solvent: DMSO-d6
[0188] -Measurement temperature: 25℃
[0189] The results are shown in Table 1 below.
[0190]
[0191] 2. Evaluation of life characteristics (cycle characteristics)
[0192] Evaluation Method
[0193] The lithium-sulfur batteries prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were charged and discharged at 60° C. under the following conditions, and the initial discharge capacity and the discharge capacity after 100 cycles were evaluated.
[0194] 1-3 cycles
[0195] Charging conditions: CC (constant current) / CV (constant voltage) (4.25 V / 0.1C current cutoff)
[0196] Discharge conditions: CC (constant current) condition 3V 0.1C
[0197] 4-100 cycles
[0198] Charging conditions: CC (constant current) / CV (constant voltage) (4.25 V / 0.2C current cutoff)
[0199] Discharge conditions: CC (constant current) condition 3V 0.2C
[0200] The results are Figure 3 and Figure 4 Shown in.
[0201] refer to Figure 3 When measured, the lithium-sulfur battery according to Example 1 has a higher initial discharge capacity than the lithium-sulfur battery according to Comparative Example 1. For example, the initial discharge capacity of the lithium-sulfur battery according to Example 1 is about 800 mAh / g, while the initial discharge capacity of the lithium-sulfur battery according to Comparative Example 1 is about 650 mAh / g.
[0202] In addition, when measured, the lithium-sulfur battery according to Example 1 has a higher discharge capacity than the lithium-sulfur battery according to Comparative Example 1 in about 10 cycles to 100 cycles, and when measured, after about 100 cycles, the lithium-sulfur battery according to Example 1 maintains a discharge capacity of more than about 600 mAh / g, while the discharge capacity of the lithium-sulfur battery according to Comparative Example 1 decreases to about 200 mAh / g.
[0203] refer to Figure 4 , when measured, the lithium-sulfur batteries according to Examples 1, 2, and 3 stably maintained a discharge capacity of about 750 mAh / g or more in about 1 cycle to 100 cycles.
[0204] In contrast, when measured, the lithium-sulfur battery according to Comparative Example 1 had a relatively low discharge capacity of about 600 mAh / g in about 1 cycle to 100 cycles, while the lithium-sulfur battery according to Comparative Example 2 maintained a discharge capacity of more than 750 mAh / g in about 70 cycles, but its discharge capacity rapidly dropped to about 520 mAh / g in about 70 cycles to 100 cycles. In addition, when measured, the lithium-sulfur battery according to Comparative Example 3 showed unstable results; when measured, it had a discharge capacity of about 800 mAh / g in about 1 cycle to 3 cycles, and after a rapid drop, had a low discharge capacity of about 250 mAh / g or less in about 4 cycles to 40 cycles, and the discharge capacity rapidly rose to about 250 mAh / g around about 25 cycles and about 30 cycles. In addition, the lithium-sulfur battery according to Comparative Example 4 maintained a discharge capacity of about 750 mAh / g for about 10 cycles, but after 70 cycles, the discharge capacity rapidly decreased, making it impossible to measure.
[0205] 3. Thermal stability evaluation
[0206] Evaluation Method
[0207] The color change and shrinkage of the separators prepared in Example 1 and Comparative Example 1 were observed with the naked eye as a function of temperature change between 100°C and 150°C.
[0208] The results are Figure 5 and Figure 6 Shown in.
[0209] refer to Figure 5 , as the temperature increases, the separator according to Comparative Example 1 exhibits shrinkage and warping, but no change in color.
[0210] refer to Figure 6 , the separator according to Example 1 showed almost no shrinkage and warpage as the temperature increased, but showed a color change due to oxidation of the polyamic acid coated on the separator.
[0211] 4. Polysulfide dissolution inhibition test
[0212] Evaluation Method
[0213] Each of the separators prepared in Example 1 and Comparative Example 1 was placed at the lid of a micro vial having an opening in which a polysulfide-containing electrolyte was present. The micro vial was placed in a chamber containing an electrolyte not containing polysulfide (bare electrolyte) and then inverted so that the lid contacted the electrolyte.
[0214] After standing for 24 hours to allow diffusion through the diaphragm, the diaphragm was removed and the surface in contact with the polysulfide-free electrolyte was analyzed by UV / visible spectroscopy. The analysis determined whether the polysulfide in the bottle was dissolved through the diaphragm.
[0215] In this case, the electrolyte (bare electrolyte) contained 1.0 M LiNO 3 in a mixed solvent of 1,3-dioxolane (DOL) and 1,2-dimethyl ether in a volume ratio (v / v) of 50:50.
[0216] The results are Figure 7 Shown in.
[0217] In the case of the diaphragm of Example 1, since the dissolution of polysulfide present in the microbottle was suppressed, no peak was found in the UV / visible spectrum or the intensity was low, while in the case of the diaphragm of Comparative Example 1, since the dissolution of polysulfide occurred, a peak was observed in the UV / visible spectrum and the intensity was high.
Claims
1. A separator for a lithium-sulfur battery, comprising: a porous polymer substrate having a plurality of pores; and a coating on at least one surface of the porous polymer substrate, the coating comprising a polyamic acid compound having a carboxyl functional group and an amide functional group, The molar ratio of the carboxyl functional group to the amide functional group is 1:0.5 to 1:
5. 2 . The lithium-sulfur battery separator according to claim 1 , wherein the molar ratio of the carboxyl functional group to the amide functional group is 1:0.75 to 1:
3. 3 . The lithium-sulfur battery separator according to claim 1 , wherein the polyamic acid compound is a polymer comprising a unit having the carboxyl functional group and the amide functional group as a repeating unit.
4. The lithium-sulfur battery separator according to claim 1, wherein the molar concentration (mmol / L) of the carboxyl functional group is 5 to 15, and The molar concentration of the amide functional groups is 8 to 20. 5 . The separator for a lithium-sulfur battery according to claim 1 , wherein the polyamic acid compound is an aromatic polyamic acid compound. 6 . The separator for a lithium-sulfur battery according to claim 1 , wherein the polydispersity index (PDI) of the polyamic acid is 2.6 to 3.
2. 7 . The lithium-sulfur battery separator according to claim 1 , wherein the polyamic acid compound having a carboxyl functional group and an amide functional group is present in the pores of the porous polymer substrate.
8. A lithium-sulfur battery, comprising: a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, The separator is a separator for a lithium-sulfur battery according to any one of claims 1 to 6.
9. A method for manufacturing a separator for a lithium-sulfur battery, the method comprising: preparing a porous polymer substrate having a plurality of pores; as well as forming a coating layer comprising a polyamic acid compound having a carboxyl functional group and an amide functional group on at least one surface of the porous polymer substrate, The formation of the coating layer containing the polyamic acid compound includes: immersing the porous polymer substrate in a first solution comprising a carboxylic dianhydride compound; as well as The porous polymer substrate immersed in the first solution is immersed in a second solution containing a diamine compound, and The molar ratio of the carboxyl functional group to the amide functional group is 1:0.5 to 1:
5.
10. The method for producing a separator for a lithium-sulfur battery according to claim 9, wherein when the coating layer comprising the polyamic acid compound is formed on the at least one surface of the porous polymer substrate, the coating layer of the polyamic acid compound is formed on the at least one surface of the porous polymer substrate while the polyamic acid compound is present in the pores. 11 . The method for manufacturing a separator for a lithium-sulfur battery according to claim 9 , wherein a molar ratio of the carboxyl functional group to the amide functional group is 1:0.75 to 1:
3.
12. The method for manufacturing a separator for a lithium-sulfur battery according to claim 9, wherein the amount of the carboxylic dianhydride compound in the first solution is 0.2 wt % to 3 wt %, and The amount of the diamine compound in the second solution is 0.2 wt % to 3 wt %. 13 . The method for producing a separator for a lithium-sulfur battery according to claim 9 , wherein the carboxyl functional group is derived from the carboxylic dianhydride compound, and the amide functional group is derived from the diamine compound.
14. The method for manufacturing a separator for a lithium-sulfur battery according to claim 13, wherein the carboxylic acid dianhydride compound comprises at least one of the following: 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-diphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, 1,2,3,4-benzenetetracarboxylic dianhydride, methylcyclohexenetetracarboxylic dianhydride, naphthalene-1,4,5,8-tetracarboxylic dianhydride or ethylenetetracarboxylic dianhydride, and The diamine compound comprises at least one of the following: p-phenylenediamine, m-phenylenediamine, 2,2'-bis(trifluoromethyl)-4,4'-biphenylenediamine, 2,2'-dimethyl-4,4'-diaminobenzidine, 4,4'-diaminodiphenyl sulfone, 2,7-diaminofluorene, 4,4-diaminooctafluorobiphenyl, 4,4'-oxydiphenylamine, 2,2'-dimethyl-4,4'-diaminobiphenyl, m-xylylenediamine, p-xylylenediamine or 4,4'-diaminobenzanilide. 15 . The method for producing a separator for a lithium-sulfur battery according to claim 9 , wherein the immersion of the porous polymer substrate in the first solution and the immersion of the porous polymer substrate in the second solution are each performed for 40 minutes to 80 minutes.
16. The method for manufacturing a separator for a lithium-sulfur battery according to claim 15, further comprising: After immersing the porous polymer substrate in the second solution, cleaning the porous polymer substrate; as well as The cleaned porous polymer substrate was dried in vacuum.
Citation Information
Patent Citations
Gutter and cultivation system based on gutter
KR1020220110367A